The THE ASSESSMENT OF CLINICAL PROFILE AND PROGNOSTIC FACTORS AMONG PATIENTS OF HEAT STROKE IN A RURAL POPULATION: A CASE SERIES - PRABHAKAR, UDAY; TRIPATHI, RUCHIKA; YADAV, RAJARAM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective was to study the clinical profile, prognostic factors, and outcomes of heat stroke in a rural population. Methods: This was a prospective, single-center, observational study. A total of 20 consecutive patients hospitalized with a diagnosis of heat stroke were included in the study over a period of 2 months from May 1, 2023, to June 30, 2023. The baseline clinical and laboratory parameters were then studied and compared between the subjects that survived and those that did not. Results: The mean age of patients was 58.8 years (standard deviation [SD]=10.4), and the mean body temperature on admission was 104.5°F (SD=0.910). Eighty percent of patients had non-exertional cause of heat stroke, whereas 20% had an exertional cause. The overall survival rate among hospitalized patients was 40%. In the multivariate analysis, serum creatinine, serum urea, serum sodium, and saturation of peripheral oxygen (SpO2) at admission independently predicted mortality. Age, sex, body temperature, systolic blood pressure, blood sugar level, and platelet count at admission were not associated with mortality. Conclusion: Heat stroke has a high hospital mortality rate. Serum sodium, serum creatinine, serum urea, and SpO2 at presentation are independent predictors of hospital mortality. Body temperature is not associated with mortality.